Reinvigorating Human Rights in Internet Governance: The UDRP Procedure Through the Lens of International Human Rights Principles - Zalnieriute, Monika (The Columbia Journal of Law & the Arts, 2020)
An international legal framework for resolving disputes between trademark owners and domain name holders, the Uniform Domain Names Disputes Resolution Policy (“UDRP”), purports to address economic interests; however, fundamental human rights are indirectly implicated in the process (for example, the rights to freedom of expression and peaceful enjoyment of one’s property) or are ingrained within the procedure itself (such as the right to due process). The UDRP was created in 1998 by the Internet Corporation for Assigned Names and Numbers (“ICANN”), which has recently adopted in its organizational bylaws a “Core Value” of respecting “internationally recognized human rights.” In light of these institutional changes, in this Article, I chart the international human rights implications of the procedural aspects of the UDRP. I will show how the UDRP’s procedural elements raise numerous due process concerns regarding the deprivation of property rights, which are recognized in international human rights instruments, and make concrete proposals to improve procedural aspects of the policy in the upcoming UDRP review in 2020. To bring the UDRP procedure in line with “internationally recognized human rights,” the upcoming review should: (1) introduce a clear choice-of law clause in the UDRP; (2) develop uniform “Supplemental Rules” at ICANN level to increase uniformity and consistency of the UDRP system; (3) introduce a requirement to disclose and publish all UDRP decisions and statistics; (4) develop uniform standards for accreditation and selection of panelists; (5) require disclosure of conflicts of interest by panelists and Dispute Resolution Providers; (6) introduce regular comprehensive UDRP reviews; (7) reform the rules around communication, and the effectiveness of notice in particular; (8) establish an appeal procedure; and (9) explicitly acknowledge access to courts.